Cardiometabolic Guidelines: Cardiovascular Risk Assessment and Management in Patients with Dysglycemia - Mohamed Hassanein; Hani Sabbour; Fatheya Al Awadi; Salah Abusnana; Bachar Afandi; Juma Al Kaabi; Alaaeldin Bashier; Francesco Cosentino; Hassan El Tamimi; Mohammed Farghali; M. Hamed Farooqi; Khadija Hafidh; et al. (Dubai Diabetes and Endocrinology Journal)
Background: Cardiovascular diseases (CVDs) are the major cause of mortality and disability in patients with type 2 diabetes mellitus (T2DM). The increased risk of major cardiovascular (CV) events in patients with T2DM causes an estimated 12-year reduction in life expectancy. Despite their heightened CV risks, most T2DM patients do not meet treatment targets for multiple CV risk factors. Moreover, in the UAE, the incidence of cardiometabolic diseases is exceedingly high, impacting young patients and leading to a high burden of premature CV events. Summary: We propose this comprehensive cardiometabolic evaluation to address both glycemic control and early diagnosis of CV complications as well as early implementation of multifactorial intensive therapies that are evidence and guideline based. Widespread utilization and implementation of the guidelines in primary diabetic care, coupled with early referral to a CV or the relevant specialists, will result in a significant reduction of CV events and CV hospitalization in the UAE population. Hence, the Emirates Diabetes and Endocrine Society with the Emirates Cardiac Society collaborated for the first time to develop these recommendations. These will aid in the early identification of CV risk factors in persons with prediabetes and diabetes, as well as their effective assessment and management. These guidelines are aimed not just at primary care physicians but also specialists, perhaps leading to a more collaborative and multidisciplinary approach to the prevention, diagnosis, and treatment of patients with diabetes and CVD. Key Message: The establishment of combined cardiometabolic clinics providing comprehensive assessment and management in every major cardiology and diabetology center, particularly in patients who have already had a CV event, where the combined involvement of a cardiologist and a diabetologist in an intensive multifactorial outpatient program is urgently required to prevent recurrent CV events. In addition, establishing a National Cardiometabolic Registry is an essential element of this recommendation.